The enforcement judge of penalties between limitations and prospects for development - Bencheikh, Nabila (Journal of Human Sciences, 2022)
The Algerian legislator elicited the idea of ​​creating the position of the enforcement judge of penalties to supervise the application of  the penalties through the French legislator, where he can be defined as a specialized judge belonging to the court of the second instance, who ensures the application of the penalties decided upon, and he can, after consulting the penalties enforcement committee, allow penalties to be reduced for prisoners having good behavior for their education and social reintegration, and his goal is to supervise the sentenced persons and follow up the progress of their lives inside and outside the penal institution, the enforcement judge of penalties has a prominent legal position in the field of application of penalties that makes him an institution in itself.